Tendency Of Developing Digital Economy in Uzbekistan - Sherov A.U; Qurbonov A.U; Ergashev M. Y (Genius Publishing Group, 2022)
The article describes the main concepts and categories of the digital economy. In particular, analyzes the development trends of the digital economy in the Republic of Uzbekistan in the context of the pandemic and the system of indicators representing the digital economy and related theoretical and practical issues. Besides, Authors give their recommendations on developing digital economy in Uzbekistan.
Keywords: Pandemic; digital economy; statistics; gross domestic product